Is sentinel node mapping useful in anorectal melanoma? - Mariolis-Sapsakos, Theodoros; Malamitsi, Julia; Yakoumakis, Emmanuel; Orfanos, Filotheos (Hell J Nucl Med, 2008)
Anorectal melanoma (AM) is a rare disease and few guidelines have been established regarding its therapeutic management. Wide local excision, or less frequently, abdominoperineal resection is the treatment of choice. We present a female patient with an excised AM who was submitted to our Nuclear Medicine department for sentinel lymph node (SLN) mapping of the area. Under rigid proctoscopy the anal scar received four submucosal injections of technetium-99m-sulfur nanocolloid of 29.6 MBq each. Lymphoscintigraphy and intraoperative gamma-probe guided detection of the SLNs followed. SLNs were localized in the inguinal basins bilaterally and were negative on histology. A wide local excision followed the above test. Thirty months postoperatively the patient developed distant metastases, underwent radiotherapy and died six months later. Without changing prognosis sentinel lymph node detection, excision and histology were important in sparing the patient a futile inguinal lymph node dissection.
Keywords: Female; Humans; Lymph Nodes; Lymphatic Metastasis; melanoma; Middle Aged; Radionuclide Imaging; Radiopharmaceuticals; Rectal Neoplasms; Sentinel Lymph Node Biopsy; Technetium Tc 99m Aggregated Albumin